Lack of a Close Relationship Between Three Strains of Human Rhinoviruses as Determined by Their RNA Sequences - Yin, Fay H. (1973)
The possible genomic homologies between three serotypes of human rhinoviruses (HRV 1A, HRV 2, and HRV 14) were investigated. First we confirmed that these viruses were unrelated by the criterion of the absence of common antigenic determinants on the surfaces of the native virions, as detected by cross-neutralization of complementfixation. RNA-RNA hybridization was then examined with purified, highly radioactive, double-stranded, replicative-form RNA and excess single-stranded virion RNA. Single-stranded RNA showed 100% homology with the minus strand from the replicative-form RNA of the same type of virus. HRV 1A, HRV 2, and HRV 14 showed low intertypic homologies; these were not significantly greater than those found between the rhinoviruses and polivirus, which were used as a negative control. The immunological relationship and the RNA homology between HRV 1A and HRV 1B were also examined by the above techniques. It was confirmed that HRV 1A and HRV 1B share some surface determinants and it was also found that HRV 1B RNA shares 70% homology with HRV 1A RNA.